The Role of Family Functioning in The Quarter-Life Crisis in Early Adulthood During The Covid-19 Pandemic - Eunike Conny Theodora Korah (Jurnal Psikologi TALENTA, 2022)
This study aims to determine the relationship between family functioning and the quarter-life crisis in early adulthood during the Covid-19 pandemic. The subjects in this study were early adult individuals aged 18-29 years with a total of 123 subjects. Data collection was done by the purposive sampling method. This research instrument uses the Family Assessment Device (FAD) Scale and the Quarter Life Crisis Quiz. Data were analyzed by the non-parametric statistical analysis technique Spearman Rho. The results of data processing obtained a correlation coefficient (p) of -0.226 with a significance value of 0.012 (p <0.05), which means that there is a negative relationship between family functioning and quarter-life crisis in early adulthood. Where if the functioning of the family is good then the quarter-life crisis is low and vice versa, if the functioning of the family is bad then the quarter-life crisis is high.